2022
DOI: 10.21926/rpm.2203018
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Forces Applied to a Superconductor in Levitation in an Inhomogeneous Magnetic Field

Abstract: Stable levitation of systems consisting of a magnetic source and a superconductor is actively investigated due to the promising applications of this technology. While huge efforts have been made for modeling these setups with numerical simulations, analytical models, in spite of their use being limited to devices with a high degree of symmetry, can bring precious information on certain characteristics of levitating systems. Summarizing our previous work in the field, we present the mean-field model that we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, measurements of the restoring force carried out on the samples investigated in this work have revealed that levitation with magnet PM70 was unstable for Z ⩽ Z L . This is due to the dependence of the restoring force on the net density of the vortices trapped in the sample [5,31], the entry of antivortices resulting in a decrease of this quantity and instability. Since stability depends also on the mean value of the magnet field in the superconductor, works are in progress to determine if an interesting trade-off between levitation force and stability can be achieved with large superconductors and magnets with suitable dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, measurements of the restoring force carried out on the samples investigated in this work have revealed that levitation with magnet PM70 was unstable for Z ⩽ Z L . This is due to the dependence of the restoring force on the net density of the vortices trapped in the sample [5,31], the entry of antivortices resulting in a decrease of this quantity and instability. Since stability depends also on the mean value of the magnet field in the superconductor, works are in progress to determine if an interesting trade-off between levitation force and stability can be achieved with large superconductors and magnets with suitable dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the mean field model can be found in [5,6,11,12]. The model considers that during the field cooling process, the magnetic flux generated by the magnet located at Z cp is channelled along vortex lines at the transition to the superconducting state at T c .…”
Section: Summary Of the Mean Field Modelmentioning
confidence: 99%
See 2 more Smart Citations